TCR recognition of peptide/MHC class II complexes and superantigens - Sundberg, Eric J. (2007)
Major histocompatibility complex (MHC) class II molecules display peptides to the T cell receptor (TCR). The ability of the TCR to discriminate foreign from self peptides presented by MHC molecules is a requirement of an effective adaptive immune response. Dysregulation of this molecular recognition event often leads to a disease state. Recently, a number of structural studies have provided significant insight into several such dysregulated interactions between peptide/MHC complexes and TCR molecules. These include TCR recognition of self peptides, which results in autoimmune reactions, and of mutant self-peptides, common in the immunosurveillance of tumors, as well as the engagement of TCRs by superantigens, a family of bacterial toxins responsible for toxic shock syndrome.